2018
DOI: 10.1016/j.dib.2018.05.096
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater quality assessment for drinking and agriculture purposes in Abhar city, Iran

Abstract: The main objective of this study is to assess the quality of groundwater for drinking consume and agriculture purposes in abhar city. The analytical results shows higher concentration of electrical conductivity (100%), total hardness (66.7%), total dissolved solids (40%), magnesium (23%), Sulfate (13.3%) which indicates signs of deterioration as per WHO and Iranian standards for drinking consume. Agricultural index, in terms of the hardness index, 73.3% of the samples in hard water category and 73.3% in sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Mg 2+ , EC, and TDS with the highest mean value of the variation index of 18.98, 20.68, and 19.04 were the most sensitive indicators in the calculation of DGWQI. Jafri et al [11] and Bawoke and Anteneh [6] showed that high EC and TDS in groundwater were the main indicators in Abhar. It means that these indicators had the highest influence on DGWQI.…”
Section: Sensitivity Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Mg 2+ , EC, and TDS with the highest mean value of the variation index of 18.98, 20.68, and 19.04 were the most sensitive indicators in the calculation of DGWQI. Jafri et al [11] and Bawoke and Anteneh [6] showed that high EC and TDS in groundwater were the main indicators in Abhar. It means that these indicators had the highest influence on DGWQI.…”
Section: Sensitivity Analysismentioning
confidence: 97%
“…However, freshwater resources are limited, and their distribution is heterogeneous. In Iran, a shortage of freshwater resources is an obstacle to economic, social, and cultural development [3,[10][11][12]. Groundwater is considered the critical resource of water for potation, agriculture, and industry in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…However, surface water samples were collected from natural lakes, depressions, ponds, canals located within the delta. Samples were collected in one-litre plastic bottles [22], which were washed and rinsed well with distilled water before use. The sampling bottles were serially numbered along with the date of collection as well as location.…”
Section: Water Samplingmentioning
confidence: 99%
“…Penilaian sampel air tanah dari berbagai parameter menunjukkan bahwa air tanah di sebagian besar wilayah studi secara kimia tidak cocok untuk tujuan minum. Jafari et al, (2018) menilai kualitas air tanah untuk konsumsi minum dan tujuan pertanian di kota Abhar. Masalah air utama di Abhar terkait dengan konduktivitas listrik dan kekerasan total air.. Barik & Pattanayak, (2019) mengevaluasi kualitas air tanah untuk memeriksa kesesuaiannya untuk tujuan irigasi dalam rangka mempertahankan ruang hijau di kota masing-masing plot menggambarkan salinitas sedang / tipe natrium rendah dan salinitas rendah / tipe natrium rendah.…”
Section: Intisariunclassified